Bringing Big Data to the Big Tent. - Goth, Gregory (Communications of the ACM, 2015)
The article discusses how open source tools can assist data science. Topic covered include the differences between investigational data science and operational data science, the various open source resources for data science such as the R statistical programming language and the Apache Spark cluster computing platform and its companion machine learning library developed at the AMPLab, and the mlpack research which shows benchmarks that are faster than those of other open source platforms such as Shogun and Weka.